PENINGKATAN AKTIVITAS PEMBELAJARAN PENDIDIKAN KEWARGANEGARAANMENGGUNAKAN MODEL CTL TEKNIK BERTUKAR PASANGAN DI SEKOLAH DASAR - Pratama, Sindang; Utami, Sri; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve the learning activities of Citizenship Education using cooperative learning model with the technique of exchange partner. The method used is descriptive method with class action research form, and collaborative nature. The location of the research took place at elementary school 16 Pontianak City, especially in class IV with research subject of teacher as researcher, and fourth grader who ordered 26 people. Science is scattered directly, with data collection tools measuring student and teacher activity to manage. Data analysis techniques used are average and percentage.This study was conducted 3 cycles with the results obtained is the ability of teachers in making learning Citizenship Education using cooperative learning model of exchange techniques starting from cycle I, namely 3.95, cycle II 4.00, and cycle III 4.00. The ability of teachers in the implementation of Civic Education learning using cooperative learning model of exchange techniques starting from cycle I, namely 3.97, cycle II 4.00, and cycle III 4.00, 3) student learning activities starting from baseline data, 19.23%, cycle I 46 , 15%, cycle II 52.20%, and cycle III 63.74%. From the data obtained shows that by using cooperative learning model of exchange techniques can improve student learning activities in grade IV of elementary school 16 Pontianak City.Keywords: Activities, Citizenship Education, Cooperative learning techniques             exchange partners